STRATEGI MENINGKATKAN DAYA SAING ALUMNI SEKOLAH TINGGI AGAMA ISLAM AL-MAWADDAH WARRAHMAH KOLAKA UNTUK MENGHADAPI MASYARAKAT EKONOMI ASEAN - Mohd Zaidi Hajazi (Jurnal Teknologi Pendidikan Madrasah, 2018)
The ASEAN Economic Community (AEC) 2015 is an ASEAN economic integrative that is free trading between ASEAN countries. A CEO of a distinguished international banking group, "There are Asian giants, who are making changes to the tectonic plate of manufacture, commerce, royalty and the global economy." ASEAN will come the horizon. The ASEAN Community is a concept that leads to the removal or inclusion of the people of ASEAN towards a more solid ASEAN integration. However, behind the thousand and one a manifest, there are various obstacles and challenges that arise. It would be a fierce competition so we can not good sleep. Every leader, regional chairman, CEO of the company, community leader, family leader and individual needs to consider new ways to compete freely. MEAs may be a good opportunity to demonstrate the quality and quantity of products and human resources (HR) at the same time may be a boomerang if not able to utilize them well. Alumnus from Islamic College (STAI) Al-Mawaddah Warrahmah Kolaka should be prepared to work on ASEAN Economic Community. Concluded that any 12 stratregy would be implemented to get this goal.